Epithelial-mesenchymal transition in gastric cancer - Huang, Lei; Wu, Ruolin; Xu, A-Man (American journal of translational research, 2015)
Gastric cancer (GC) is one of the most common malignancies worldwide with poor prognosis for lack of early detection and effective treatment modalities. The significant influence of tumor microenvironment on malignant cells has been extensively investigated in this targeted-therapy era. Epithelial-mesenchymal transition (EMT) is a highly conserved and fundamental process that is critical for embryogenesis and some other pathophysiological processes, especially tumor genesis and progression. Aberrant gastric EMT activation could endow gastric epithelial cells with increased mesenchymal characteristics and less epithelial features, and promote cancer cell stemness, initiation, invasion, metastasis, and chemo-resistance with cellular adhesion molecules especially E-cadherin concomitantly repressed, which allows tumor cells to disseminate and spread throughout the body. Some pathogens, stress, and hypoxia could induce and aggravate GC via EMT, which is significantly correlated with prognosis. GC EMT is modulated by diverse micro-environmental, membrane, and intracellular cues, and could be triggered by various overexpressed transcription factors, which are downstream of several vital cross-talking signaling pathways including TGF-β, Wnt/β-catenin, Notch, etc. microRNAs also contribute significantly to GC EMT modulation. There are currently some agents which could suppress GC EMT, shedding light on novel anti-malignancy strategies. Investigating potential mechanisms modulating GC cell EMT and discovering novel EMT regulators will further elucidate GC biology, and may provide new biomarkers for early GC detection and potentially efficient targets for preventative and curative anti-GC intervention approaches to prevent local and distant invasions.
Gesehen am 23.05.2017